Design of sensing radio frequency identification (RFID) tag - Ma, Chenyu (Nanyang Technological University, 2023)
In this dissertation, it presents a RFID-based PM2.5 air quality detection system. The RFID front-end of the system is consisted of a tag antenna and a RFID chip operating in the UHF frequency band. The main structure of the system consists of a low-power microcontroller, MSP430FR5969(serving as the control core). It includes a high accuracy and small-sized PM2.5 sensor, PMS5003, for real-time PM2.5 data acquisition. Additionally, there is a RFID front-end composed of a UHF band RFID chip and a dipole-matched antenna, which we designed and simulated. The microcontroller continuously collects data from the PM2.5 sensor and stores it upon power-up. The RFID front-end and RFID reader communicate with each other. When the RFID front-end receives a read command from the reader, the microcontroller interrupts its original process and initiates a four-wire SPI communication with the RFID chip. The collected PM2.5 data is then input and stored in the registers of the RFID chip. The chip, in turn, utilizes backscatter technology to transmit this data to the RFID reader.